DeconStructing the IDR 271 Trillion Scandal: Fraud Hexagon’s Perspective on the Governance of State-Owned Mining Enterprises - Gumelar, Taofik Muhammad; Alamsyah, Rudi (Journal Research of Social Science, Economics, and Management, 2026)
Corruption remains a fundamental obstacle to economic development and governance across various industrial sectors, including mining. Indonesia continues to be categorized as a country with a high level of corruption, particularly within extractive industries. The corruption scandal involving PT Timah Tbk represents one of the largest cases illustrating the complexity of governance challenges and significant oversight weaknesses, with a 2023 audit by the Supreme Audit Agency (Badan Pemeriksa Keuangan/BPK) reporting state losses amounting to IDR 271 trillion. This study aimed to analyze the application of the Fraud Hexagon model in detecting indications of corruption at PT Timah Tbk, a strategic mining company in Indonesia, by examining six key elements: pressure, opportunity, rationalization, capability, arrogance, and collusion. This study employed a qualitative method with a case study approach, utilizing primary data from interviews and secondary data consisting of financial reports, BPK audit findings, investigative media reports, and Supreme Court rulings. Data analysis was conducted using thematic analysis, content analysis, and the Miles and Huberman data analysis model, with findings validated through data source triangulation. The results indicate that arrogance functions as a primary triggering factor, as individuals in strategic positions may perceive themselves as superior and beyond legal accountability, while collusion reinforces corrupt practices through structured networks involving state-owned enterprise officials, private-sector actors, and government regulators. The implications of this study highlight the need to strengthen technology-based internal control systems and enhance managerial accountability to prevent similar scandals from recurring in Indonesia’s strategic mining sector.